Perubahan Luas Lahan Sawah menjadi Non Sawah di Wilayah Joglosemar - Natasha Diofanny; Jawoto Sih Setyono (Jurusan Perencanaan Wilayah dan Kota, 2016)
Urbanisation process in Joglosemar region of Central Java has more or less affected the size of paddy field. Data from CSB (Central Statistical Board) estimate that during the last decade the land used for rice field has declined around 5,424 hectares. At the same time the number of people living in urban areas has increased by around 3 million people. If the conversion of rice field continues, it will likely to have an impact on food security for the region as well as its neighboring areas. This research aims to analyse the factors that contribute to the change in paddy field production areas in Joglosemar region. The research applies quantitative method to analyse the rate of conversion by using linier regression technique. Based on the analysis, it is found that the average rate of rice field conversion is 0.24% per year while the main cause of the conversion is the urbanization process. It is also found that the industrialisation process and land productivity have insignificant contribution to the conversion process. From the findings, it can be estimated that if the urbanization rate reaches 4.64% annually as it happens recently, in the next decade until 2030 Joglosemar region will experience deficit of rice supply.